2013
DOI: 10.29173/cais572
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Impact of Culture on the Design of Arabic Government Websites

Abstract: This study examines selected design characteristics of government Web interfaces from three Arab countries using Hofstede’s cultural dimensions. Organizational and graphical elements from 30 ministry websites from Egypt, Lebanon, and Saudi Arabia were examined using content analysis method. The results suggest that Hofstede’s model of culture does not fully reflect the design characteristics of these interfaces.Cette étude examine un ensemble de caractéristiques dans la conception d’interfaces Web de trois pay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Recently, in analyzing cultural similarities and differences in English‐language and Chinese‐language website designs from data collected on 223 Fortune Global 500 company websites, Chang () found that cultural differences exist in power distance, uncertainty avoidance, individualism/collectivism, and long‐term and short‐term dimensions. However, Khashman and Large (), while examining Arabic government websites with Hofstede's cultural dimensions, concluded that his cultural model is not fully reflected in the design characteristics of the websites examined.…”
Section: Literature Researchmentioning
confidence: 99%
“…Recently, in analyzing cultural similarities and differences in English‐language and Chinese‐language website designs from data collected on 223 Fortune Global 500 company websites, Chang () found that cultural differences exist in power distance, uncertainty avoidance, individualism/collectivism, and long‐term and short‐term dimensions. However, Khashman and Large (), while examining Arabic government websites with Hofstede's cultural dimensions, concluded that his cultural model is not fully reflected in the design characteristics of the websites examined.…”
Section: Literature Researchmentioning
confidence: 99%